Rare Case of Metastatic Colorectal Cancer to Uretral Meatus with Rapid Progression and Fatal Outcomes - Benatiya, Marwane Andaloussi; Asri, Zakaria El; Rais, Ghizlane (European Scientific Journal, ESJ, 2018)
Urethral metastases are extremely rare. A few cases of uretral metastasis in the literature have been found to arise from the colon. Because of the rarity of uretral metastasis and its similarity to primary uretral neoplasms, diagnosis is rarely evoqued. We report here a case of a 46-yearold female admitted to our hospital with complaints of rectal bleeding, bowel distension and urinary symptoms. Clinical examination revealed rectal mass associated with meatus urethral tumor. A biopsy yielded a diagnosis of rectal adenocarcinoma with metastasis to urethral meatus, and tumor cells were strongly and uniformly positive for CK20 and CDX2 at immunohistochemical analysis. A general examination has shown a sigmoid tumor with hepatic metastatic lesion. One month after diagnosis, the tumor grew rapidly, with hepatic invasion and therefore the patient was treated only by palliative care. She died from liver failure one month later. Although urethral metastasis originating from colon is rare, this entity is increasingly described. The synchronous character and the location of the metastasis in the uretral meatus, are two remarkable characteristics described in this case report. The purpose of presenting this case report is to raise awareness among clinicians to consider this clinical entity as a differential diagnosis when urethral mass is identified.